All-solid-state negative electrode sheet, all-solid-state battery, and electric device
Patent Information
- Application Number
- CN202610970634.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-30
AI Technical Summary
在全固态负极极片中,负极主材、固态电解质及导电剂之间为固-固接触,接触点有限,难以形成连续高效的电子传输网络,导致极片整体电子电导率偏低
[0015]复合导电剂中较高长径比的纤维状导电材料具有较高的长径比和优异的本征电导率,能够在负极活性物质层内部构建长程连续的电子传输通道;较低长径比的纤维状导电材料具有适中的长径比和良好的分散性,能够在较高长径比的导电材料构建的骨架之间形成短程搭接,填充局部的导电盲区。两者协同作用,形成了从纳米尺度到微米尺度的多层次、三维连续导电网络。该三维导电网络有效解决了全固态负极极片中因固-固接触导致的电子传输路径不连续问题。在本方案中电子能够通过长程通道快速跨越负极活性物质层,并借助短程搭接高效注入每一颗负极活性材料颗粒和固态电解质颗粒的表面,极大减少了电子在颗粒间跳跃时的势垒和损耗。因此,复合导电剂可提升负极极片整体的电子电导率,进而降低极化内阻,从而使电池在大电流充放电时更稳定、循环过程中衰减更慢,最终改善了全固态电池的快充性能和循环寿命。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This application belongs to the field of battery technology, specifically relating to an all-solid-state negative electrode sheet, an all-solid-state battery, and an electrical device. Background Technology
[0002] All-solid-state batteries combine high energy density and high safety, making them a key development direction for next-generation battery cell technology. In all-solid-state negative electrode sheets, the contact between the negative electrode material, solid electrolyte, and conductive agent is solid-solid, with limited contact points, making it difficult to form a continuous and efficient electron transport network, resulting in low overall electronic conductivity of the electrode sheet. This low overall electronic conductivity can trigger polarization during charging and discharging, especially under high-rate (e.g., above 2C) fast charging conditions. Electrons cannot be transported to the surface of the active material in time, leading to incomplete capacity utilization, degraded rate performance, and potentially exacerbated side reactions and reduced cycle life. Summary of the Invention
[0003] The purpose of this application is to provide an all-solid-state negative electrode sheet, an all-solid-state battery, and an electrical device. The negative electrode sheet improves its own electronic conductivity through the synergistic optimization of composite conductive agents, thereby improving the fast charging performance and cycle life of the all-solid-state battery.
[0004] This application provides an all-solid-state negative electrode sheet, which includes: a negative electrode current collector and a negative electrode active material layer; wherein, the negative electrode active material layer is disposed on at least one side of the negative electrode current collector; the negative electrode active material layer includes a composite conductive agent; the composite conductive agent comprises at least two fibrous conductive materials with different aspect ratios.
[0005] In one embodiment, the fibrous conductive material with a higher aspect ratio in the composite conductive agent is a single-walled carbon nanotube, used to construct a long-range conductive framework; the fibrous conductive material with a lower aspect ratio in the composite conductive agent is a vapor-grown carbon fiber, used to fill the gaps between the framework to form short-range overlaps; wherein, the aspect ratio is the ratio of the length to the diameter of the fibrous conductive material.
[0006] In one embodiment, the composite conductive agent satisfies at least one of the following: in the composite conductive agent, the mass ratio of the single-walled carbon nanotubes to the vapor-grown carbon fibers is 1:100 to 1:5; the aspect ratio of the single-walled carbon nanotubes is 500 to 50000; and the aspect ratio of the vapor-grown carbon fibers is 25 to 500.
[0007] In one embodiment, the composite conductive agent satisfies at least one of the following: the diameter of the single-walled carbon nanotube is 1~10nm and the length is 5~50um; the diameter of the vapor-grown carbon fiber is 100~200nm and the length is 5~50μm.
[0008] In one embodiment, the negative electrode active material layer further includes: a negative electrode active material, a solid electrolyte, and a binder.
[0009] In one embodiment, the negative electrode active material layer satisfies at least one of the following: the negative electrode active material includes at least one of carbon-based materials and silicon-based materials; the solid electrolyte is a sulfide solid electrolyte; and the binder includes at least one of styrene-ethylene / butene-styrene block copolymer, styrene-ethylene-butadiene copolymer, styrene-butadiene rubber, polyvinylidene fluoride, polyacrylic acid, polytetrafluoroethylene, and carboxymethyl cellulose.
[0010] In one embodiment, the negative electrode active material layer satisfies at least one of the following: the sulfide solid electrolyte includes at least one of Li6PS5Cl, Li6PS5Br, and Li3PS4; in the negative electrode active material layer, the mass ratio of the negative electrode active material, the solid electrolyte, the composite conductive agent, and the binder is 75~85:10~35:0.5~3:1~3.
[0011] This application also provides a method for preparing an all-solid-state negative electrode sheet, the method comprising: dispersing at least two fibrous conductive materials with different aspect ratios in a solvent to obtain a composite conductive agent dispersion; obtaining a negative electrode slurry based on the composite conductive agent dispersion; and coating the negative electrode slurry onto at least one side of a negative electrode current collector to obtain an all-solid-state negative electrode sheet.
[0012] This application also provides an all-solid-state battery, including the all-solid-state negative electrode sheet described above, or the all-solid-state negative electrode sheet prepared by the above preparation method.
[0013] This application also provides an electrical device, which includes the above-described all-solid-state battery, and the all-solid-state battery is used to supply power to the electrical device.
[0014] This application provides an all-solid-state negative electrode sheet, which includes: a negative electrode current collector and a negative electrode active material layer; wherein, the negative electrode active material layer is disposed on at least one side of the negative electrode current collector; the negative electrode active material layer includes a composite conductive agent; the composite conductive agent comprises at least two fibrous conductive materials with different aspect ratios.
[0015] The composite conductive agent, with its high aspect ratio fibrous conductive material exhibiting both high aspect ratio and excellent intrinsic conductivity, enables the construction of long-range continuous electron transport channels within the negative electrode active material layer. Conversely, the lower aspect ratio fibrous conductive material, with its moderate aspect ratio and good dispersibility, allows for short-range overlaps between the framework constructed by the higher aspect ratio conductive material, filling localized conductive dead zones. The synergistic effect of these two materials forms a multi-layered, three-dimensional continuous conductive network ranging from the nanoscale to the microscale. This three-dimensional conductive network effectively solves the problem of discontinuous electron transport paths caused by solid-solid contacts in all-solid-state negative electrode sheets. In this scheme, electrons can rapidly traverse the negative electrode active material layer through long-range channels and efficiently inject into the surface of each negative electrode active material particle and solid electrolyte particle via short-range overlaps, significantly reducing the potential barrier and losses during electron hopping between particles. Therefore, the composite conductive agent can improve the overall electronic conductivity of the negative electrode sheet, thereby reducing polarization resistance. This results in greater battery stability during high-current charging and discharging, slower degradation during cycling, and ultimately improved fast-charging performance and cycle life of all-solid-state batteries. Detailed Implementation
[0016] The present invention will be further described in detail below through specific embodiments. In the following embodiments, many details are described to facilitate a better understanding of this application. However, those skilled in the art will readily recognize that some features may be omitted in different situations, or may be replaced by other elements, materials, or methods. In some cases, certain operations related to this application are not shown or described in the specification. This is to avoid obscuring the core parts of this application with excessive description. For those skilled in the art, detailed description of these related operations is not necessary; they can fully understand the related operations based on the description in the specification and general technical knowledge in the art.
[0017] Furthermore, the features, operations, or characteristics described in the specification can be combined in any suitable manner to form various embodiments. At the same time, the steps or actions in the method description can be rearranged or adjusted in a manner obvious to those skilled in the art. Therefore, the various orders in the specification are only for clearly describing a particular embodiment and do not imply a necessary order, unless otherwise stated that a particular order must be followed.
[0018] This application provides an all-solid-state negative electrode sheet, which includes: a negative electrode current collector and a negative electrode active material layer; wherein, the negative electrode active material layer is disposed on at least one side of the negative electrode current collector; the negative electrode active material layer includes a composite conductive agent; the composite conductive agent comprises at least two fibrous conductive materials with different aspect ratios.
[0019] The composite conductive agent, with its high aspect ratio fibrous conductive material exhibiting both high aspect ratio and excellent intrinsic conductivity, enables the construction of long-range continuous electron transport channels within the negative electrode active material layer. Conversely, the lower aspect ratio fibrous conductive material, with its moderate aspect ratio and good dispersibility, allows for short-range overlaps between the framework constructed by the higher aspect ratio conductive material, filling localized conductive dead zones. The synergistic effect of these two materials forms a multi-layered, three-dimensional continuous conductive network ranging from the nanoscale to the microscale. This three-dimensional conductive network effectively solves the problem of discontinuous electron transport paths caused by solid-solid contacts in all-solid-state negative electrode sheets. In this scheme, electrons can rapidly traverse the negative electrode active material layer through long-range channels and efficiently inject into the surface of each negative electrode active material particle and solid electrolyte particle via short-range overlaps, significantly reducing the potential barrier and losses during electron hopping between particles. Therefore, the composite conductive agent can improve the overall electronic conductivity of the negative electrode sheet, thereby reducing polarization resistance. This results in greater battery stability during high-current charging and discharging, slower degradation during cycling, and ultimately improved fast-charging performance and cycle life of all-solid-state batteries.
[0020] In one embodiment, the fibrous conductive material with a higher aspect ratio is single-walled carbon nanotubes (SWCNTs), used to construct a long-range conductive framework; the fibrous conductive material with a lower aspect ratio is vapor-grown carbon fiber (VGCF), used to fill the spaces between the frameworks to form short-range overlaps.
[0021] In one embodiment, the mass ratio of SWCNT to VGCF in the composite conductive agent is 1:100 to 1:5. Within this mass ratio range, SWCNT and VGCF can form an optimal synergistic conductive network.
[0022] Specifically, in the composite conductive agent, the mass ratio of SWCNT to VGCF is 1:100, 1:60, 1:30, 1:20, 1:5, or any value within the above range.
[0023] In one embodiment, the aspect ratio of the single-walled carbon nanotubes is 500 to 50000. Single-walled carbon nanotubes with this aspect ratio can span multiple particles in the negative electrode active material layer to construct a long-range continuous electron transport channel.
[0024] Specifically, the aspect ratio of single-walled carbon nanotubes is 500, 8000, 20000, 50000 or any value within the above range.
[0025] In one embodiment, the single-walled carbon nanotubes have a diameter of 1~10nm and a length of 5~50um. In addition to the long-range conductivity mentioned above, the single-walled carbon nanotubes in this range can also adapt to the volume change of the negative electrode active material particles in a flexible winding manner, avoid puncturing the SEI film, and achieve a synergistic improvement in the efficiency of the conductive network and the stability of the electrode structure.
[0026] Specifically, the diameter of the single-walled carbon nanotubes is 1 nm, 3 nm, 6 nm, 10 nm or any value within the above range, and the length is 5 μm, 25 μm, 50 μm or any value within the above range.
[0027] In one embodiment, the aspect ratio of the vapor-grown carbon fibers is 25-500. This dimensional parameter allows single-walled carbon nanotubes to overlap short-range within the long-range framework constructed by the single-walled carbon nanotubes, filling localized conductive dead zones. Its moderate aspect ratio ensures good dispersibility while avoiding excessive aggregation.
[0028] Specifically, the aspect ratio of vapor-grown carbon fibers is 25, 250, 500, or any value within the above range.
[0029] In one embodiment, the diameter of the vapor-grown carbon fiber is 100-200 nm, and the length is 5-50 μm. This diameter range allows the vapor-grown carbon fiber to be 1-2 orders of magnitude thicker than single-walled carbon nanotubes (SUVs), enabling it to embed itself in the gaps between SUVs without entanglement. This length range allows the length of the vapor-grown carbon fiber to match that of the SUVs, achieving effective short-range overlap between the SUV framework. Thus, the vapor-grown carbon fiber and the SUVs form a multi-level conductive network with varying thicknesses and lengths, providing short-range filling within the blind areas of the long-range SUV framework while maintaining good dispersion due to the appropriate aspect ratio.
[0030] Specifically, the diameter of the vapor-grown carbon fiber is 100nm, 150nm, 200nm or any value within the above range, and the length is 5μm, 15μm, 40μm, 50μm or any value within the above range.
[0031] In one embodiment, the mass ratio of the negative electrode active material, solid electrolyte, composite conductive agent, and binder in the negative electrode active material layer is 75~85:10~35:0.5~3:1~3. This ratio achieves a synergistic improvement in both the electronic and ionic conductivity of the negative electrode sheet.
[0032] Specifically, in the negative electrode active material layer, the mass ratio of negative electrode active material, solid electrolyte, composite conductive agent, and binder is 78~82:18~27:1~2:2~3.
[0033] In one embodiment, the negative electrode active material includes at least one of carbon-based and silicon-based materials. Carbon-based materials (such as artificial graphite and natural graphite) have good cycle stability, while silicon-based materials (such as silicon-carbon materials, silicon-oxygen materials, and elemental silicon) have higher specific capacity. Both can be used alone or in combination to balance the battery's energy density and cycle life.
[0034] In one embodiment, the solid electrolyte is a sulfide solid electrolyte (such as Li6PS5Cl, Li6PS5Br, Li3PS4). Sulfide solid electrolytes have extremely high ionic conductivity, and their good flexibility also facilitates the formation of a tight solid-solid contact interface with composite conductive agents and negative electrode active materials.
[0035] In one embodiment, the binder includes at least one selected from styrene-ethylene / butene-styrene block copolymer, styrene-ethylene-butadiene copolymer, styrene-butadiene rubber, polyvinylidene fluoride, polyacrylic acid, polytetrafluoroethylene, and carboxymethyl cellulose. The above binder can maintain the structural integrity of the negative electrode sheet while ensuring compatibility with the solid electrolyte.
[0036] In one embodiment, the thickness of the negative electrode current collector is 6~10μm. The negative electrode current collector within this thickness range can reduce the proportion of inactive materials while ensuring the mechanical strength of the current collector, thereby improving the mass energy density of the battery.
[0037] Specifically, the thickness of the negative electrode current collector is 6μm, 8μm, 10μm or any value within the above range.
[0038] In one embodiment, the negative electrode current collector is copper foil or carbon-coated copper foil; of course, other conductive materials that can carry and support the negative electrode active material layer are also acceptable.
[0039] In one embodiment, the thickness of the negative electrode active material layer is 20~150μm. Within this thickness range, the conductive network constructed by SWCNT and VGCF can fully exert its synergistic effect to ensure efficient electron transport in the thick electrode, thereby achieving a balance between high areal capacity and good rate performance.
[0040] Specifically, the thickness of the negative electrode active material layer is 20 μm, 80 μm, 150 μm or any value within the above range.
[0041] This application also provides a method for preparing an all-solid-state negative electrode sheet, comprising the following steps S1 to S3: S1. A composite conductive agent dispersion is obtained by dispersing at least two fibrous conductive materials with different aspect ratios in a solvent.
[0042] In one embodiment, the step specifically includes: adding single-walled carbon nanotubes and vapor-grown carbon fibers to a solvent, and obtaining a composite conductive agent dispersion by ultrasonic dispersion.
[0043] In one embodiment, the solvent includes xylene or toluene.
[0044] In one embodiment, the ultrasonic dispersion conditions include: power of 500-1000W, frequency of 20-40kHz, and time of 30-90min. These ultrasonic dispersion conditions enable the uniform dispersion of single-walled carbon nanotubes and vapor-grown carbon fibers in a solvent without disrupting their aspect ratio structure, while avoiding excessive aggregation or breakage, ensuring that both form the desired conductive network in the negative electrode.
[0045] Specifically, the ultrasonic dispersion power is 500W, 800W, 1000W or any value within the above range, the frequency is 20kHz, 30kHz, 40kHz or any value within the above range, and the time is 30min, 50min, 90min or any value within the above range.
[0046] In one embodiment, a dispersant, such as carboxymethylcellulose (CMC), a surfactant, or a styrene-ethylene-butylene-styrene block copolymer (SEBS), may also be added to the solvent to ensure the dispersion of single-walled carbon nanotubes and vapor-grown carbon fibers in the solvent.
[0047] S2. Obtain the negative electrode slurry based on the composite conductive agent dispersion.
[0048] In one embodiment: A negative electrode active material, a solid electrolyte, and a binder are added to a composite conductive agent dispersion, and the mixture is stirred in a planetary mixer or a double planetary mixer. After standing for 0.5 to 2 hours, a dispersion treatment is performed to obtain a uniform negative electrode slurry.
[0049] In one embodiment, the stirring conditions include: a stirring speed of 1500~3000 rpm and a stirring time of 2~4 h. These stirring conditions can ensure the mixing efficiency and uniformity of the above materials.
[0050] Specifically, the stirring speed is 1500 rpm, 2200 rpm, 3000 rpm or any value within the above range, and the stirring time is 2 h, 3 h, 4 h or any value within the above range.
[0051] In one embodiment, the dispersion processing conditions include: a rotation speed of 2000~3000 rpm and a time of 30~60 s. These dispersion conditions can ensure the uniformity of the negative electrode slurry.
[0052] Specifically, the dispersed conditions include a rotational speed of 2000 rpm, 2500 rpm, 3000 rpm or any value within the above range, and a time of 30 s, 50 s, 60 s or any value within the above range.
[0053] S3. Coat the negative electrode slurry on at least one side of the negative electrode current collector, and dry it to obtain an all-solid negative electrode sheet.
[0054] Specifically, this includes: in an inert atmosphere glove box, applying the negative electrode slurry onto the negative electrode current collector using a scraper, and then drying it to obtain an all-solid-state negative electrode sheet.
[0055] In one embodiment, the coating speed is 1~5m / min. This coating speed range can ensure that the negative electrode slurry is fully leveled and has a uniform thickness on the surface of the negative electrode current collector.
[0056] Specifically, the coating speed is 1 m / min, 3 m / min, 5 m / min or any value within the above range.
[0057] In one embodiment, the drying conditions include: a drying temperature of 90~110°C and a drying time of 0.5~2h. These drying conditions can gently remove the solvent from the negative electrode slurry without damaging the solid electrolyte structure.
[0058] In one embodiment, the drying temperature is 90°C, 100°C, 110°C or any value within the above range, and the drying time is 0.5h, 1h, 2h or any value within the above range.
[0059] It should be noted that the substances or their contents used in this method have been explained in the product description above, and will not be repeated here to avoid repetition.
[0060] This application also provides an all-solid-state battery, including an all-solid-state negative electrode.
[0061] In one embodiment, the all-solid-state battery can be a single cell, a battery module, or a battery pack.
[0062] It should be noted that all-solid-state batteries also include necessary components such as positive electrode plates and solid electrolyte layers. The solid electrolyte layer is placed between the negative electrode plates and the positive electrode plates to provide a channel for ion transport between the positive and negative electrodes, while blocking electron transport, thereby avoiding short circuits.
[0063] This application also provides an electrical device that includes an all-solid-state battery for powering the device.
[0064] In one embodiment, the electrical device is not limited to mobile phones, tablets, laptops, electric toys, electric vehicles, new energy vehicles, robots, etc.
[0065] To enable those skilled in the art to better understand this application, the following detailed description, in conjunction with specific embodiments, further illustrates the application. Obviously, the described embodiments are merely some, not all, of the embodiments described. It should be understood that the specific embodiments are only used to explain the application, and are not intended to limit the scope of the application.
[0066] Example 1 A method for preparing an all-solid-state battery, comprising: 1. Preparation of the negative electrode: SWCNT (diameter 1 nm, length 50 μm, length-to-diameter ratio 50000) and VGCF (diameter 100 nm, length 50 μm, length-to-diameter ratio 500) were added to 500 mL of xylene, along with 5 g of dispersant SEBS. The mixture was ultrasonically dispersed (800 W, 40 kHz, 60 min) to obtain a composite conductive agent dispersion. Then, artificial graphite, silicon carbide material, solid electrolyte, and binder SEBS were sequentially added to the composite conductive agent dispersion. The mixture was stirred at 2500 rpm for 3 h in a dual planetary mixer, allowed to stand for 1 h, and then dispersed again at 2500 rpm for 45 s to obtain the negative electrode slurry. Finally, the negative electrode slurry was coated onto copper foil and dried at 100 °C for 1 h to obtain the negative electrode sheet.
[0067] 2. Preparation of the positive electrode sheet: The positive electrode active material LiNi... 0.8 Co 0.1 Mn0.1O2, sulfide solid electrolyte Li6PS5Cl, and conductive agent VGCF were mixed in a mass ratio of 70:28:2. The mixed powder was then placed in a mortar and ground thoroughly for 30 minutes to ensure uniform mixing. The uniformly mixed powder was then transferred to a mold and cold-pressed at 300 MPa in a glove box (under an inert atmosphere) to obtain the positive electrode sheet.
[0068] 3. Preparation of solid electrolyte layer: Li6PS5Cl solid electrolyte powder was placed in a mold and uniaxially cold-pressed into a dense solid electrolyte layer of 600μm in a glove box. The pressing pressure was 300MPa.
[0069] 4. Battery encapsulation: In a glove box (Ar atmosphere, H2O<0.1ppm, O2<0.1ppm), the positive electrode, solid electrolyte layer, and negative electrode are stacked sequentially into the mold. After the mold is closed, an axial pressure of 1MPa is applied to the mold and held for 3 minutes to form a tight solid-solid contact interface between the layers, thus completing the encapsulation and obtaining an all-solid-state battery.
[0070] Examples 2-5 The difference from Example 1 is that the components and their contents of the negative electrode sheet in step 1 are detailed in Table 1.
[0071] Example 6 The difference from Example 1 is that: the diameter of SWCNT is 10nm, the length is 5um, and the length-to-diameter ratio is 500; the diameter of VGCF is 200nm, the length is 5um, and the length-to-diameter ratio is 25.
[0072] Comparative Examples 1-2 The difference from Example 1 is that the components and their contents of the negative electrode sheet in step 1 are detailed in Table 1.
[0073] The following performance tests were conducted on the all-solid-state batteries in the above embodiments and comparative examples, and the test data are shown in Table 2.
[0074] I. Fast Charging Performance Test At 25°C, the all-solid-state battery was charged to 4.2V at a constant current and constant voltage of 0.1C (cutoff current 0.01C), and then discharged to 2.5V at a constant current of 0.1C, and the cycle was repeated 3 times.
[0075] Constant current and constant voltage charging was performed at 0.2C and 2C rates (cutoff current 0.01C), followed by constant current discharge at 0.1C to 2.5V after each charge. The charging capacity at each rate was recorded, and the capacity retention rate relative to the 0.2C charging capacity was calculated. The capacity retention rate is calculated as follows: (Charging capacity at each rate / 0.2C charging capacity) × 100%.
[0076] II. Cycle life test At 25°C, the all-solid-state battery was charged at 0.1C constant current and constant voltage to 4.2V (cutoff current 0.01C), and discharged at 0.1C to 2.5V, undergoing three activation cycles. Subsequently, it was charged at 1C constant current and constant voltage to 4.2V (cutoff current 0.01C), and then discharged at 1C constant current to 2.5V for cycle testing. The specific capacity of the first discharge and the specific capacity of the 200th cycle were recorded, and the capacity retention rate was calculated. The capacity retention rate is calculated as: (Specific capacity of the Nth cycle discharge / Specific capacity of the first cycle discharge) × 100%.
[0077] Table 1. Parameters of the negative electrode sheet in the embodiments and comparative examples.
[0078] Table 2 Performance data of all-solid-state batteries in the examples and comparative examples
[0079] As shown in Table 2, compared to the comparative example, the battery in the embodiment achieved a capacity retention rate of 87.5% at 2C rate and a cycle retention rate of 86.3% after 200 cycles. These data fully demonstrate that the synergistic effect of SWCNT and VGCF can effectively improve the overall electronic conductivity of the negative electrode, thereby improving the fast-charging performance and cycle life of the all-solid-state battery.
[0080] The endpoints and any values of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or thresholds should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0081] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0082] Although embodiments of this application have been shown and described, those skilled in the art will understand that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of this application, the scope of which is defined by the claims and their equivalents.
Claims
1. A fully solid-state negative electrode sheet, characterized in that, The all-solid-state negative electrode sheet includes: a negative electrode current collector and a negative electrode active material layer; The negative electrode active material layer is disposed on at least one side of the negative electrode current collector; the negative electrode active material layer includes a composite conductive agent; the composite conductive agent comprises at least two fibrous conductive materials with different aspect ratios.
2. The all-solid-state negative electrode sheet according to claim 1, characterized in that, The composite conductive agent contains a high aspect ratio fibrous conductive material, which is a single-walled carbon nanotube used to construct a long-range conductive framework; the composite conductive agent contains a low aspect ratio fibrous conductive material, which is a vapor-grown carbon fiber used to fill the spaces between the frameworks to form short-range overlaps. Wherein, the aspect ratio is the ratio of the length to the diameter of the fibrous conductive material.
3. The all-solid-state negative electrode sheet according to claim 2, characterized in that, The composite conductive agent satisfies at least one of the following: In the composite conductive agent, the mass ratio of the single-walled carbon nanotubes to the vapor-grown carbon fibers is 1:100 to 1:5; The aspect ratio of the single-walled carbon nanotubes is 500~50000; The aspect ratio of the vapor-grown carbon fiber is 25~500.
4. The all-solid-state negative electrode sheet according to any one of claims 2 to 3, characterized in that, The composite conductive agent satisfies at least one of the following: The single-walled carbon nanotubes have a diameter of 1~10nm and a length of 5~50um; The vapor-grown carbon fiber has a diameter of 100~200nm and a length of 5~50μm.
5. The all-solid-state negative electrode sheet according to any one of claims 1 to 4, characterized in that, The negative electrode active material layer also includes: negative electrode active material, solid electrolyte, and binder.
6. The all-solid-state negative electrode sheet according to claim 5, characterized in that, The negative electrode active material layer satisfies at least one of the following: The negative electrode active material includes at least one of carbon-based materials and silicon-based materials; The solid electrolyte is a sulfide solid electrolyte; The adhesive includes at least one of styrene-ethylene / butene-styrene block copolymer, styrene-ethylene-butadiene copolymer, styrene-butadiene rubber, polyvinylidene fluoride, polyacrylic acid, polytetrafluoroethylene, and carboxymethyl cellulose.
7. The all-solid-state negative electrode sheet according to claim 6, characterized in that, The negative electrode active material layer satisfies at least one of the following: The sulfide solid electrolyte includes at least one of Li6PS5Cl, Li6PS5Br, and Li3PS4; In the negative electrode active material layer, the mass ratio of the negative electrode active material, the solid electrolyte, the composite conductive agent, and the binder is 75~85:10~35:0.5~3:1~3.
8. A method for preparing an all-solid-state negative electrode sheet, characterized in that, The method includes: A composite conductive agent dispersion is obtained by dispersing at least two fibrous conductive materials with different aspect ratios in a solvent. A negative electrode slurry is obtained based on the composite conductive agent dispersion; The negative electrode slurry is coated on at least one side of the negative electrode current collector to obtain an all-solid-state negative electrode sheet.
9. An all-solid-state battery, characterized in that, Includes the all-solid-state negative electrode sheet according to any one of claims 1 to 7, or the all-solid-state negative electrode sheet prepared by the preparation method according to claim 8.
10. An electrical appliance, characterized in that, The electrical device includes the all-solid-state battery of claim 9, which is used to power the electrical device.
